Evaluation of Green Open Space Needs Based on Oxygen Requirements: Implementation of the 13th Goal of The SDGs 2030 - Rahma Musyawarah; Mutmainnah Mutmainnah; Nurul Ilmi Rasjusti (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Kendari City is an area experiencing rapid population growth and urbanization. Over the past two decades, the population growth rate in this area has been 1.70%/year. This condition has resulted in the conversion of green land into residential, commercial, and industrial land, which has an impact on the decline in the availability of Green Open Space and has an effect on the phenomenon of climate change. This study utilizes Sentinel 2A satellite imagery and the Normalized Difference Vegetation Index (NDVI) transformation to map the distribution of Green Open Space in Kendari City. Identification of the need for Green Open Space is carried out based on oxygen needs using the modified Gerakis (1974) formula. The results of the study show that: 1) Kendari City has a total area of ​​Green Open Space based on NDVI analysis of 19,458.94 hectares; 2) based on the analysis of oxygen needs for residents, animals, and motorized vehicles, the total area of ​​Green Open Space needed in Kendari City is 1,927.79 hectares; and 3) the implementation of the results of this study can support the achievement of Goal 13 of the SDGs 2030 through strengthening environmental policies, increasing public awareness, and involving local communities in environmental conservation efforts. This shows that the green open space available in Kendari City is sufficient to accommodate oxygen needs so that additional green open space is not needed. Therefore, the focus of Kendari City's future policies can be shifted to the management and optimization of existing green open spaces to support broader sustainable development goals.